Psychometric validation of anti-clot treatment scale and treatment satisfaction questionnaire for medication version II in Japanese patients with atrial fibrillation. (3rd August 2019) - Watanabe-Fujinuma, Emi; Banderas, Benjamin F.; Koretsune, Yukihiro; Kumagai, Koichiro; Uchiyama, Shinichiro; Yamashita, Takeshi; Yasaka, Masahiro; Akiyama, Sayako; Briere, Jean-Baptiste; Dickie, Gavin; Cano, Stefan J.
Abstract: Aims: The Anti-Clot Treatment Scale (ACTS) and Treatment Satisfaction Questionnaire for Medication version II (TSQM-II) are validated treatment satisfaction patient-reported outcome (PRO) instruments. The ACTS includes two domains: Burdens and Benefits; the TSQM-II includes four: Effectiveness, Side Effects, Convenience, and Global Satisfaction. Japanese-language versions of the ACTS and TSQM-II have been developed and linguistically validated. This study aimed to assess their psychometric properties in Japanese patients with atrial fibrillation (AF). Materials and methods: ACTS and TSQM-II data from 534 patients with AF were collected in a Japanese post-marketing surveillance study of a direct oral-anticoagulant, rivaroxaban. Four key psychometric properties, in line with best practice guidelines from the US Food and Drug Administration, were examined using traditional psychometric methods: acceptability, scaling assumptions, reliability (i.e. internal consistency reliability, test-retest reliability), and construct validity (i.e. convergent validity and known groups). Results: ACTS Burdens and Benefits and TSQM-II Effectiveness, Convenience, and Global Satisfaction scales were found to be acceptable (e.g. item-level missing data at baseline <4%), with all scales having good internal consistency (Cronbach's alpha > 0.80). test-retest reproducibility intraclass correlation coefficients for the ACTS Burdens and Benefits were 0.59 and 0.65, respectively, and between 0.54–0.61 for the TSQM-II scales. Known-groups validity for the ACTS and TSQM-II was supported by differences in scale scores by positive and negative impact ( p < 0.05). Correlations between the ACTS and TSQM-II (convergent validity) were lower than expected (range r = 0.09–0.48), but in line with the original ACTS development study. Limitations: Evaluation of test-retest reproducibility was limited by assessment period, which was longer (3 months) than recommended guidelines (usually up to 2 weeks). Conclusions: Overall, Japanese versions of ACTS and TSQM-II scales satisfied internal consistency reliability and traditional validity criteria. Our study supports the ACTS and TSQM-II as appropriate PRO instruments to measure satisfaction with anticoagulant treatment in Japanese patients with AF. Trial registration: NCT01598051, clinicaltrials.gov; registered April 20, 2012.